‘Tall and lithe’–The wage-height premium in the Victorian and Edwardian British railway industry - Anderson, Peter (Elsevier, 2017)
Studies in anthropometrics continue to find a wage-height premium in modern economies despite most productivity not contingent on physical strength. These authors argue that height is a proxy for cognitive and non-cognitive abilities, which earns the positive return. In this paper, I collected data on over 2,200 English and Welsh railwaymen from staff ledgers to test if the same relationship held during the Victorian and Edwardian period. Using an OLS model, it is found that a wage-height premium existed. Applying the same model to different subgroups of railwaymen, it was found that the premium only accrued to taller men working in skilled grades that required a higher cognitive and non-cognitive skill to strength ratio. No such premium existed in the physically taxing entry-level railway grades. A probit regression finds that taller Great Western signalmen working in Wales did not have a lower probability of receiving a fine upon committing an infraction; a finding that contradicts heightism as an explanation of the wage-height premium. I conclude that taller railwaymen benefited because height indirectly measured their cognitive and non-cognitive abilities, not their strength.